MINIINVASIVE APPROACHES IN VARICOSE VEIN SURGERY - Herman, Jiri; Duda, Miloslav (Biomedical papers, 1999)
vein perforatorsAuthors present their own experience with the treatment of chronic venous insufficiency. Between August 1995and November 1998 they operated on 318 patients for the disease of venous system. In 28 patients (i.e. 9%) theyperformed 30 miniinvasive interventions - 8 x retroperitoneoscopic lumbar sympathectomy and 22 x endoscopicsubfascial dissection of vein perforators. The rest of patients (91%) were treated by means of classical operationson superficial venous system.
Keywords: Minimally invasive surgery / Chronic venous insufficiency / Lumbar sympathectomy / Endoscopic dissectio of